2002
DOI: 10.1016/s0031-0182(01)00500-4
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary variability of ocean circulation in the southeastern South Atlantic inferred from the terrigenous sediment record of a drift deposit in the southern Cape Basin (ODP Site 1089)

Abstract: During Leg 177 of the Ocean Drilling Program, an expanded sequence of Pliocene to Holocene calcareous muds was recovered at Site 1089 on a drift deposit in the southern Cape Basin (SE South Atlantic). The reconstruction of detrital sources and modes of sediment transport gives insight into the operational modes of regional current systems in response to climate variability over the last 590 kyr, as inferred from sedimentological and mineralogical parameters of the terrigenous sediment fraction. Terrigenous sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
52
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 64 publications
11
52
0
1
Order By: Relevance
“…Time-series of IRD flux are expressed as clast abundances per area and time unit [# cm-2 kyr-I ] , by integrating counted IRD abundances at equal time increments of 1 kyr. The proportions of non-carbonate silt and clay (referred to as terrigenous mud) were determined by grain-size separation in settling tubes, after sieving the bulk samples through a 63-llm mesh for separation of the sand fraction and dissolution of carbonate with 10-% acetic acid (Brehrne 1992;Kuhn and Diekmann 2002a, b). Silt grain-size analyses were conducted on sediment cores from the southern Cape Basin (Site 1 089/PS2821) and the northwestern Weddell Sea (PS2515).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-series of IRD flux are expressed as clast abundances per area and time unit [# cm-2 kyr-I ] , by integrating counted IRD abundances at equal time increments of 1 kyr. The proportions of non-carbonate silt and clay (referred to as terrigenous mud) were determined by grain-size separation in settling tubes, after sieving the bulk samples through a 63-llm mesh for separation of the sand fraction and dissolution of carbonate with 10-% acetic acid (Brehrne 1992;Kuhn and Diekmann 2002a, b). Silt grain-size analyses were conducted on sediment cores from the southern Cape Basin (Site 1 089/PS2821) and the northwestern Weddell Sea (PS2515).…”
Section: Methodsmentioning
confidence: 99%
“…The non-carbonate silt fraction was dispersed in sodium-polyphosphate solution and measured with a 'Micromeritics SediGraph 5000E' to determine the grain-size distribution in lilO-Phi steps and hence the proportion of sortable silt (particle sizes 63-10 Ilm) in the mud fraction (McCave et al 1995). The bias of the terrigenous grain-size signal caused by biosiliceous particles in the non-carbonate mud fraction is negligible, because of relatively low opal concentrations that range between 3% and 7% in sediment core PS1575 (Bonn et al 1998) and are ~15 % in the record of Site 1989IPS2821 (Kuhn and Diekmann 2002a, b). Moreover, no correlation exists between opal concentrations and grain-size variability for the latter record with the slightly elevated opal concentrations (Kuhn and Diekmann 2002b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] Several studies of the Southeast Atlantic have concluded that the supply of Agulhas water to the Atlantic was reduced substantially during glacial times [Flores et al, 1999;Kuhn and Diekmann, 2002;Peeters et al, 2004;Franzese et al, 2006]. Furthermore, as the Agulhas system and the Drake Passage are the two primary avenues for return flow to the North Atlantic [Gordon et al, 1992], the glacial reduction in supply of Agulhas water may have been compensated for by increased supply via the Drake Passage.…”
Section: Pa4216mentioning
confidence: 99%
“…In addition to the elemental analyses of the XRF-scanned data, we use the detrital Al/Ti ratio in discrete XRF bulk sediment samples to reflect changes in terrigenous provenance (Kuhn and Diekmann, 2002;Scher et al, 2015). Al/Ti ratio varies between 17-21, with the highest values found within F1 and the lowest in F2 (Fig.…”
mentioning
confidence: 99%